Ultrasound Biomarkers for Sarcopenia: What Can We Tell So Far? - Mirón Mombiela, Rebeca; Vucetic, Jelena; Rossi, Federica; Tagliafico, Alberto Stefano (Seminars in Musculoskeletal Radiology, 2020)
Sarcopenia is a disease characterized by decreased skeletal muscle mass, strength, and loss of function that can impair quality of life and increase physical disability, adverse metabolic effects, and mortality. This review familiarizes the reader with ultrasound (US)-based biomarkers for sarcopenia with a discussion of these topics: why assessing sarcopenia is relevant for radiologists, how to evaluate muscle structure with US, the current challenges or pitfalls of these biomarkers, and the implications of all the available evidence. It summarizes the most up-to-date literature on the pathophysiology behind the use of these US-based biomarkers, the biomarkers themselves, and a protocol used for their assessments. The article also describes representative examples that reflect modern practice in the field. Imaging is routinely used in clinical practice, and radiologists can play an important role in the evaluation of geriatric patients, providing an unprecedented opportunity to improve decision support in sarcopenia prevention and treatment.
Keywords: sarcopenia; ultrasound; computed tomography; muscle; biomarkers